GAS6 signaling tempers Th17 development in patients with multiple sclerosis and helminth infection - Ortiz Wilczyñski, Juan Manuel (2020)
Multiple sclerosis (MS) is a highly disabling neurodegenerative autoimmune condition in which an unbalanced immune response plays a critical role. Although the mechanisms remain poorly defined, helminth infections are known to modulate the severity and progression of chronic inflammatory diseases. The tyrosine kinase receptors TYRO3, AXL, and MERTK (TAM) have been described as inhibitors of the immune response in various inflammatory settings. We show here that patients with concurrent natural helminth infections and MS condition (HIMS) had an increased expression of the negative regulatory TAM receptors in antigen-presenting cells and their agonist GAS6 in circulating CD11bhigh and CD4+ T cells compared to patients with only MS. The Th17 subset was reduced in patients with HIMS with a subsequent downregulation of its pathogenic genetic program. Moreover, these CD4+ T cells promoted lower levels of the co-stimulatory molecules CD80, CD86, and CD40 on dendritic cells compared with CD4+ T cells from patients with MS, an effect that was GAS6-dependent. IL-10+ cells from patients with HIMS showed higher GAS6 expression levels than Th17 cells, and inhibition of phosphatidylserine/GAS6 binding led to an expansion of Th17 effector genes. The addition of GAS6 on activated CD4+ T cells from patients with MS restrains the Th17 gene expression signature. This cohort of patients with HIMS unravels a promising regulatory mechanism to dampen the Th17 inflammatory response in autoimmunity.